(untitled) (Third Sector Social Economic Review, 2023)
The Covid-19 pandemic has greatly affected the daily life of all humanity. With quarantines and economic pauses, consumers’ behavior began to change soon after the pandemic was declared. The air transport sector has been one of the sectors most affected by the Covid-19 pandemic. This study was conducted to identify and classify changes in consumer behavior in the air transport industry due to COVID-19. The aim is to find gaps in the literature, to provide easy and single-source access to research on this subject, and to be prepared for possible COVID-19-like cases in the future. For this purpose, research on changes in consumer behavior in air transport due to COVID-19 was gathered from the academic databases, analyzed using content analysis method and attempted to be classified systematically. This study enables researchers, managers, and consumers to reach research on this subject in a single study, and thus to find out the studies on the consumers’ behavioral changes that occurred in the air transport sector before, during and after the pandemic as a whole.